Within-season variation of fitness in elite youth female soccer players - Taylor, J. M.; Portas, M. D.; Wright, M. D.; Hurst, C.; Weston, M. (Journal of Athletic Enhancement, 2012)
Study Background: The within-season variation in fitness measures of elite youth female soccer players (<18 years of age) has not been investigated previously. Further knowledge of this area could allow more effective periodization of training, whilst also enabling coaches to design appropriate long-term athlete development models. This study investigated the within-season variation of fitness test performance in elite youth female soccer players.